Relationship Between Immersive Learning and Proficiency Level in Machine Operations Among Technology Education Students in Higher Institutions in Anambra State - Ogunmola; Chigbata (Journal of Research in Industrial Technology and Educational Studies, 2026)
This study examined the relationship between immersive learning and proficiency level in machine operations among technology education students in higher institutions in Anambra State. This study adopted a correlational survey research design. The population of the study consisted of 253 Mechanical Technology Education Students in Anambra State. A sample size of 155 students using simple random sampling technique was obtained. The instrument for data collection was a structured questionnaire. The questionnaire was validated by three experts with the reliability Coefficients of 0.71 and 0.81 respectively, established using Cronbach alpha’s method. Data collected were analyzed using inferential statistics. Specifically, the Pearson Product-Moment Correlation Coefficient was employed to answer the two research questions. The findings of the study revealed a moderate positive relationship (r = 0.395) between the use of Virtual Reality (VR) simulations and proficiency in machine operations and a strong positive relationship (r = 0.656) between the use of Augmented Reality (AR) tools and proficiency in machine operations among Technology Education students. Based on the findings, it was recommended that universities should integrate both VR and AR tools into Technology Education curricula, with particular emphasis on AR due to its stronger influence on proficiency in machine operations.